The Relationship between Resistance to Temptation and Common Styles of Thinking Among University Students in Jordan - Al-Tarawneh, Sabri; Al-Qudah, Mohammed (Jordan Journal of Educational Sciences, 2014)
This study aimed at measuring the relationship between the resistance to temptation and common styles of thinking among the students of Jordanian universities. The sample of the study consisted of (1701) male and female students, from Jordan University and Mutah University, selected by clustered stratified random sample. To fulfill the aims of the study, measure of Resistance to Temptation and Measure of Styles of Thinking by Harrison & Bramison were used in this study. Results showed that the degree of resistance to temptation was low, and the highest value for the thinking styles was for the Idealistic, then Pragmatic, then Analytic, then Synthetic. and Realistic. Results also showed statistically significant differences in the resistance to temptation attributed to the variable of sex in favor of females. Results also showed statistically significant differences in the thinking styles of Idealistic and Analytic attributed to the variable of sex in favor of males in Idealistic style of thinking, and in favor of females in Analytic style of thinking, and to the variable of college in Synthetic and Pragmatic styles of thinking in favor of scientific colleges students. The relationship between the styles of thinking and the resistance to temptation was positive and significant